A hierarchical Building Management System for temperature's optimal control and electric vehicles' integration. (January 2023) - Bianco, Giovanni; Delfino, Federico; Ferro, Giulio; Robba, Michela; Rossi, Mansueto
Highlights: The paper proposes a new bi-level Building Management System that integrates electric vehicles' scheduling and temperature control in rooms. A distributed approach based on distributed alternating direction method of multipliers is presented. A real case study has been considered. Abstract: A bi-level building management system for optimal temperature control and scheduling of electric vehicles in a smart building is proposed. The architecture allows considering automated decisions, both for operational management and real-time control, minimizing costs and the dissatisfaction of different requirements (electric vehicles' charging, demand response). A particular feature of the building management system is that it includes a model for electric vehicles' charging (both for vehicles-to-grid and classical electric vehicles) that can consider three-phases unbalanced systems and the inputs required by the Charging Stations, i.e., the set point for the current for each plugin use. Moreover, a distributed approach for the optimal control of fan coils is proposed that allows adjusting the temperature in each room. The developed building management system has been tested at the Savona Campus in a building characterized by a photovoltaic field, a geothermal heat pump, EVs charging infrastructure, thermal storage, and a fan coil circuit. The tests carried out at the Campus show that the proposed algorithm allows a reduction of the daily costs of about 20% with respect to a simple heuristic, without compromising the fulfillment of the charging requests of the electric vehicles. The savings can be increased till close to 35% if a demand response is also exploited.